Pattern Recognition c - Mester, Rudolf; Felsberg, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 33rd Symposium of the German Association for Pattern Recognition, DAGM 2011, held in Frankfurt/Main, Germany, in August/September 2011. The 20 revised full papers and 22 revised poster papers were carefully reviewed and selected from 98 submissions. The papers are organized in topical sections on object recognition, adverse vision conditions challenge, shape and matching, segmentation and early vision, robot vision, machine learning, and motion. The volume also includes the young researcher's forum, a section where a carefully jury-selected ensemble of young researchers present their Master thesis work.
Keywords: Computer science; Computer software; Information systems; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Pattern Recognition; Image Processing and Computer Vision; Artificial Intelligence (incl. Robotics).; Computer Graphics; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).